Early psychosocial parent–infant interventions and parent–infant relationships after preterm birth–a scoping review - Leppänen, Marika; Korja, Riikka; Rautava, Päivi; Ahlqvist-Björkroth, Sari (Frontiers in Psychology, 2024)
Objective Early psychosocial interventions for preterm infants and their parents are diverse. This study aimed to structure the knowledge on psychosocial parent–infant interventions and to identify gaps in the intervention studies. Methods We included studies on early (during first year of life) psychosocial parent–infant interventions with parent–infant relationship outcomes after preterm birth (< 37 weeks). We excluded studies that did not focus on preterm infants, failed to indicate the studied intervention and outcomes, were not written in English, were not controlled or peer-reviewed studies, or did not provide essential information for eligibility. The search included studies published between January 2000 and March 2024 in PubMed and PsycINFO. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in reporting. Psychosocial parent–infant intervention studies were classified adapting the International Classification of Health Interventions (ICHI) and the Template for Intervention Description and Replication (TIDieR). Results The included 22 studies reported data from 18 different interventions with preterm infants (< 37 weeks). Studies excluded preterm infants with health risks (19/22, 86%), with very low gestational age and/or birth weight (7/22, 32%), and/or mothers with psychosocial risks (14/22, 64%). Of the 18 interventions, 12 (67%) were classified as counseling, 3 (17%) as emotional support, 2 (11%) as psychotherapeutic, and 1 (6%) as educational. The parent–child relationship was assessed using 30 different methods and varying time points up to 18 months of age. Most studies (17/22, 77%) reported positive changes in the parent–child relationship favoring the intervention group. Conclusion We identified four types of interventions to influence parenting behavior; the most used was counseling. All four intervention types showed positive effects on parent–infant relationships, although the preterm populations studied were selective, the effects were evaluated using different methods, and the follow-up periods were short. These findings indicate a need for studies with standardized methods, longer follow-up, and less-restricted preterm populations to develop guidelines for all families with preterm infants.